PENGARUH PEMBERIAN PAKAN ITIK DENGAN LIMBAH UDANG DAN LIMBAH KULIT KACANG KEDELAI YANG DIBERI PROBIOTIK TERHADAP PRODUKSI DAN WARNA KUNING TELUR - Sindu Akhadiarto (Jurnal Teknologi Lingkungan, 2010)
The objective of this study was to utilize the superiority of agricultural waste in form of soybean hull and shrimp wastes and their combination on egg layer duck. This feed contains starbio probiotic functions for fiber digestion (soybean hull waste) and chitin (from shrimp waste). The expectation was that there would be duck ration which is able to increase egg production and quality and brighter reddish egg-yolk which is attractive and full of nutritions. The research was conducted in three stages. Stage I is Nutrient Digestional Value Test on the formula of soybean hull and shrimp wastes mixture on Duck Feed Contained Starbio." Stage II : experiment on "Mixture Formulation of soybean hull and shrimp wastes mixture on Duck Feed Contained Starbio Probiotik for Increasing The Performance of Egg Layer Duck" and III experiment on "The Production of Reddish Duck Egg-Yolk With Feed Contained soybean hull and Shrimp Wastes Mixture". The experiment concluded that : I) the provision of soybean hull andshrimp had significant effects on digestability of feed dried materials, but conversely had no effects on protein digestability and crude fiber, as well as on egg produktion and quality.There was no interaction between two materials in the treatment. 2) Shrimp waste tended to have effects on daily egg production of egg layer duck; 3) Yellow color of the eggs couldn't change to be reddish yet, since xanthophyl content had already lost in over-dried and alreadyexpired shrimp wastes.Key Words : shrimp waste, soybean hull, probiotic, egg-yolk color